Planned Yellow Fever Primary Vaccination Is Safe and Immunogenic in Patients With Autoimmune Diseases: A Prospective Non-interventional Study - Valim, Valéria; Machado, Ketty Lysie Libardi Lira; Miyamoto, Samira Tatiyama; Pinto, Arthur Dalmaso; Rocha, Priscila Costa Martins; Serrano, Erica Vieira; Dinis, Valquiria Garcia; Gouvêa, Sônia Alves; Dias, João Gabriel Fragoso; Campi-Azevedo, Ana Carolina; Teixeira-Carvalho, Andréa; Peruhype-Magalhães, Vanessa; et al. (Frontiers in Immunology, 2020)
Yellow Fever (YF) vaccination is suggested to induce a large number of adverse events (AE) and suboptimal responses in patients with autoimmune diseases (AID); however, there have been no studies on 17DD-YF primary vaccination performance in patients with AID. This prospective non-interventional study conducted between March and July, 2017 assessed the safety and immunogenicity of planned 17DD-YF primary vaccination in patients with AID. Adult patients with AID (both sexes) were enrolled, along with healthy controls (HC), at a single hospital (Vitória, Brazil). Included patients were referred for planned vaccination by a rheumatologist; in remission, or with low disease activity; and had low level immunosuppression or the attending physician advised interruption of immunosuppression for safety reasons. The occurrence of AE, neutralizing antibody kinetics, seropositivity rates, and 17DD-YF viremia were evaluated at various time points (day 0 (D0), D3, D4, D5, D6, D14, and D28). Individuals evaluated (n = 278), including patients with rheumatoid arthritis (RA; 79), spondyloarthritis (SpA; 59), systemic sclerosis (8), systemic lupus erythematosus (SLE; 27), primary Sjögren’s syndrome (SS; 54), and healthy controls HC (51). Only mild AE were reported. The frequency of local and systemic AE in patients with AID and HC did not differ significantly (8% vs. 10% and 21% vs. 32%; p = 1.00 and 0.18, respectively).. Patients with AID presented with late seroconversion profiles according to kinetic timelines of the plaque reduction neutralization test (PRNT). PRNT-determined virus titers (copies/mL) [181 (95% confidence interval (CI), 144–228) vs. 440 (95% CI, 291–665), P = 0.004] and seropositivity rate (78% vs. 96%, p = 0.01) were lower in patients with AID after 28 days, particularly those with SpA (73%) and SLE (73%), relative to HC. The YF viremia peak (RNAnemia) was 5–6 days after vaccination in all groups. In conclusion, consistent seroconversion rates were observed in patients with AID and our findings support that planned 17DD-YF primary vaccination is safe and immunogenic in patients with AID.